Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

BMI229

  • 3 years ago

Solve. 2x2 – 8x – 12 = 0 x = 1 ± 2 x = 2 ± x = 2 ± x = 2 ± 2

  • This Question is Closed
  1. dusty
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    By factoring, we obtain: 2(x² - 4x - 6) = 0 Since the polynomial is unfactorable, we can apply quadratic formula x = (-b ± √(b² - 4ac))/2a, along with ax² + bx + c = 0, to obtain: a = 1 b = -4 c = -6 x = (-(-4) ± √((-4)² - 4*1*-6))/(2*1) ==> (4 ± √(16 + 24))/2 ==> (4 ± √40)/2 ==> (4 ± √(10*4))/2 . . . . . . . . . . . . . . .Note that √4 = 2. ==> (4 ± 2√10)/2 . . . . . . . . . . . . . . . . Factor ==> 2(2 ± √10)/2 . . . . . . . . . . . . . . . . Reduce ==> 2 ± √10 Therefore, x = 2 ± √10

  2. gorv
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    yeah @dusty is right

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy